Identification and validation of four photodynamic therapy related genes inhibiting MAPK and inducing cell cycle alteration in squamous cell carcinoma - Zhao, Yingchao; Dong, Jianxiang; Liao, Yuxuan; Wang, Hongyi; Zhou, Dawei; Kang, Jian; Chen, Xiang (Frontiers in Oncology, 2022)
Introduction: Cutaneous squamous cell carcinoma (cSCC) is the second most common skin cancer, and photodynamic therapy (PDT) is a promising modality against cSCC. This study investigated the impact of PDT on the MAPK pathway and cell cycle alternation of cSCC, as well as the related molecular mechanisms. Method: Expressing mRNA profiles data set GSE98767, GSE45216, and GSE84758 were acquired from the GEO database. The functions of differently expressed genes (DEGs) were enriched by Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. Least absolute shrinkage and selection operator (Lasso) analysis were used to establish a diagnosis model based on GSE98767. Correlation analysis and protein-protein interaction (PPI) network were used to evaluate the relationship between cSCC-PDT-related genes and the MAPK pathway. Single sample gene set enrichment analysis (ssGSEA) was performed on GSE98767 to estimate MAPK activation and cell cycle activity. Finally, the effect of MAPK activation on the cell cycle was explored in vitro. Result: Four cSCC-PDT-related genes DUSP6, EFNB2, DNAJB1, and CCNL1 were identified as diagnostic markers of cSCC, which were upregulated in cSCC or LC50 PDT-protocol treatment and negatively correlated with MAPK promoter. Despite having a smaller MAPK activation score, cSCC showed higher cell cycle activity. The PDT treatment suppressed the G1 to G2/M phase in JNK overexpressed A431 cells. Conclusion: CCNL1, DNAJB1, DUSP6, and EFNB2 were identified as potential PDT target genes in cSCC treatment, whose potential therapeutic mechanism was inhibiting the MAPK pathway and inducing cell cycle alternation.